(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2019)
The land demands the proper organization of accounting when deciding management questions. Using land in production process agro-industrial enterprizes detached it in the part of objects of accounting. In the modern conditions of economic development the demand arose to improve the existing organization-economic mechanism of regulation of efficient use of lands on all levels of management, in all branches and spheres of national economy. The modern stage of development of agrarian relations determines the necessity of continuing the problems research related with generalization of historical experience of realization of business accounting of land recources in the country, of deepening tasks and improvement of methodological aspects of its realization. In Ukraine the accounting is realized with necessary completeness and detail depending on certain groups of lands characteristics according to the Law of Ukraine ‘On the state land cadastre’. The cadaster acquired the status of the only state geoinformation system. The cadastre must contain the information about lands situated in the limits of the state border of Ukraine, their target use, the limitation in their use and also the data on quantity and quality characteristics of lands, their estimation about lands distribution among owners and users. The questions of lands accounting in the conditions of formation and strengthening the market become especially actual in the relation with demand to receive by users the exact and authentic information about the state, quality and estimation of land resources, the efficiency of their use in consolidation of lands. The liberalization of lands relations will ensure the market formation of price on land, will positively influence on competitive relations, the rise of innovation activity of farms for formation of competitive agro-industrial complex and increase in domestic investment that leads to economic growth.